Evaluation of effect of aluminum oxide on flexural strength and surface roughness of conventional heat-cure denture base resin - Madhu Ranjan (Wolters Kluwer Medknow Publications, 2021)
Purpose: Acrylic denture base tends to fracture frequently during their service due to poor strength. The surface roughness of denture base is a critical property because denture base with rough surface will cause accumulation of food particles ,thereby leading plaque retention . Microbes such as candida albicans are seen inhabitating the surface. Materials and Methods: Conventional heat cure denture base reins(DPI) and heat cure denture base resin with incorporation of 15wt% aluminium oxide was studied in two groups with 20 samples each. A mold of size 65 mm × 10 mm × 3 mm (ISO Standard) was obtained by investing brass rectangles. About forty specimens were prepared. Specimens were divided into two groups (n = 20) coded A and B. Group A was the control group (n = 20) without addition of aluminum oxide. Group B was the experimental group (n = 20) with addition of 15 wt % aluminum oxide. All the specimens were stored in distilled water for 14 days. The flexural strength was measured using a three-point bending test in a universal testing machine, and the surface roughness was measured using contact-type profilometer. Results: Incorporation of 15wt% aluminum oxide leads to a significant increase in flexural strength and surface roughness of conventional heat-cure denture base resin.